“Canine tracker”; an app based on android platform for localisation of impacted maxillary canines using digital panoramic radigraphs - G.A. Adersh, MDS; S. Sibi; L.K. Surej Kumar, MDS, FDS RCPS (GLASGOW); NikhilM. Kurien, MDS (Journal of Oral Biology and Craniofacial Research)
The panoramic radiographs for localisation of impacted canines are now mostly available in the digital form. It is difficult to apply the localisation techniques in the digital format especially when it is viewed and diagnosed using smart phones. So in this paper we are describing about an app we created based on the android platform. Using this app three localisation methods can be applied by using multiple tools.